2000
DOI: 10.1246/cl.2000.890
|View full text |Cite
|
Sign up to set email alerts
|

The NMR Spectroscopic Evaluation of Immobility of a Crowd of Porphyrin Rings Combined with Dendritic Poly(l-lysine)s

Abstract: Since the dendritic poly(l-lysine)s combining eight to thirty-two free base-porphyrins showed split circular dichroism at the Soret band in toluene/N,N-dimethylformamide (9/1, v/v), the immobility of porphyrin rings was evaluated by 1H NMR measurements in terms of the peak width at half-height and spin-lattice relaxation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Furthermore, work within our group developed a noncovalent system using a dendrimer as a scaffold to support a large number of external porphyrins . Other examples include a number of symmetrical porphyrin arrays, such as the aromatic polyether porphyrin dendrimer prepared by Aida et al These types of multiporphyrin architectures have been shown to exhibit energy transfer efficiencies of over 90%; however, they are limited by the time-consuming nature of the synthesis involved.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, work within our group developed a noncovalent system using a dendrimer as a scaffold to support a large number of external porphyrins . Other examples include a number of symmetrical porphyrin arrays, such as the aromatic polyether porphyrin dendrimer prepared by Aida et al These types of multiporphyrin architectures have been shown to exhibit energy transfer efficiencies of over 90%; however, they are limited by the time-consuming nature of the synthesis involved.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of a Water-Soluble Dendrimer with a Porphyrin − Fullerene System. An l -lysine dendrimer was chosen to attach to the porphyrin−fullerene system in this study because it is a typical and well-characterized dendrimer and can easily be incorporated with various functional groups. , We have synthesized both the porphyrin-linked l -amino acid, ( N -α-( tert -butoxycarbonyl)- N ‘ -ε-(4-(tritolylporphyrin-5-yl)benzoyl)- l -lysine), 27a, and the fullerene-linked l -amino acid, ( l -2-( tert -butoxycarbonylamino)-8-(fulleropyrrolidinyl)octanoic acid), in enantiomeric pure forms to be used as monomers for the l -amino acid dendrimers. Mimicking the recent report on the porphyrin−fullerene system,13c we adopted a system with a pair of porphyrins and a fullerene (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Scheme outlines the synthesis of a water-soluble dendrimer 6 . The core is the fullerene-containing l -amino acid 1 , which connected NH−(CH 2 ) 6 −NHCO 2 CH 2 Ph at the C-terminal as a potential linker to a certain functional group in the future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[121][122][123][124][125][126] In addition, more complex system 29a has been reported (Chart 11), which possesses 16 zinc porphyrin (P Zn ) units on one hemisphere and 16 free-base porphyrin (P FB ) units on the other hemisphere of a fifthgeneration poly(L-lysine) dendrimer. 127,128 Photoexcitation of the P Zn units results in energy transfer to the P FB units with an efficiency of 43%. As a reference compound, dendrimer 29b, which contains randomly mixed P Zn and P FB units on the dendrimer surface, shows a much higher energy transfer efficiency (85%).…”
Section: Energy Migration and Transfer In Dendrimers With Multiple Pomentioning
confidence: 99%